2018
DOI: 10.18294/pm.2018.1900
|View full text |Cite
|
Sign up to set email alerts
|

Índice de actitud hacia la investigación y disposición a la titulación por tesis

Abstract: La Licenciatura en inglés en modalidad virtual está enfocada a la profesionalización de maestros de inglés. Además de la titulación por tesis, la institución acepta otras modalidades, que los alumnos han preferido para titularse. Aun así, los índices de titulación del programa son bajos. En esta investigación, se realizó un análisis cuantitativo para determinar el índice de actitud que tienen los alumnos de la Licenciatura en inglés en modalidad virtual hacia la investigación. Se identificó su concepto sobre l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
1
1
0
3
Order By: Relevance
“…Finally, from the results obtained regarding the level of attitude towards formative research developing applications with augmented reality, it was identified that 34.375% of students showed a high attitude, 31.250% a regular attitude, while 34.375% showed a low attitude. These results coincide with findings identified by Obermeier (2018) in his study on the index of attitude towards research and willingness to graduate by thesis, and who points out that most students have a low or medium index. In this same line of opinion, Olivera (2020), in his research on attitudes towards research in psychology students, identified that 67% of students show an unfavourable attitude, while only 33% of students show a favourable attitude.…”
Section: Discussionsupporting
confidence: 90%
“…Finally, from the results obtained regarding the level of attitude towards formative research developing applications with augmented reality, it was identified that 34.375% of students showed a high attitude, 31.250% a regular attitude, while 34.375% showed a low attitude. These results coincide with findings identified by Obermeier (2018) in his study on the index of attitude towards research and willingness to graduate by thesis, and who points out that most students have a low or medium index. In this same line of opinion, Olivera (2020), in his research on attitudes towards research in psychology students, identified that 67% of students show an unfavourable attitude, while only 33% of students show a favourable attitude.…”
Section: Discussionsupporting
confidence: 90%
“…La primera hipótesis, la cual planteaba que la actitud promedio hacia la investigación sería favorable, fue rechazada debido a que de acuerdo con los datos obtenidos la media de las actitudes en los universitarios fue de regular a desfavorable; estos resultados concuerdan parcialmente con los hallazgos de Obermeier (2019), donde los universitarios señalaron una actitud baja hacia la investigación, y difieren de lo hallado por Olivera (2020), quien señala que en los estudiantes de Psicología participantes en su estudio existió una actitud favorable hacia la investigación. Al respecto, Paredes-Proaño y Moreta-Herrera (2020) exponen que la actitud negativa hacia la investigación en estudiantes universitarios puede ser explicada por el deficiente interés y motivación que influye al iniciar una investigación, desarrollarla y llegar a la culminación de la misma; por ello la idea de que la investigación es difícil o tediosa suele cambiar cuando se explica la importancia que tiene en la formación profesional (Obermeier, 2018).…”
Section: Discussionunclassified
“…Es conveniente señalar, que la investigación no debe ser considerada únicamente como un proceso sustantivo de la universidad, sino que representa también una función en la labor profesional de tal manera que está relacionada con la preparación del estudiante para enfrentar las exigencias del desarrollo científico-técnico contemporáneo (Barbón & Bascó, 2016); en ese sentido, se sugiere incentivar las habilidades y formación investigativa desde los primeros años de pregrado en las asignaturas (Fernández & Villavicencio, 2017), así como incorporar a los y las estudiantes universitarias en grupos de investigación para que estén familiarizados con ellos y motivar con ello su participación en congresos y seminarios de investigación (Obermeier, 2018).…”
Section: Discussionunclassified
“…This was a correlational study and it was found that a deeper insight from students was necessary to understand the reasons why they do not consider writing a dissertation. It was concluded that students have low attitude towards research and they consider that the teachers and the institution do not encourage them to conduct research (Obermeier, 2017). The present study was conducted to provide a deeper insight of the phenomenon and evaluate if this situation prevails in the indoors program of the same institution.…”
Section: Introductionmentioning
confidence: 93%